Investigating genetic population structure and the role of social structure on residency, mating strategies and associations in a small population of bottlenose dolphins (Tursiops truncatus) under pressure - James, Bridget Susan (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2021.